2018
DOI: 10.1002/aelm.201800071
|View full text |Cite
|
Sign up to set email alerts
|

3D Multifunctional Composites Based on Large‐Area Stretchable Circuit with Thermoforming Technology

Abstract: decade, substantial efforts were devoted to the research and development of the nextgeneration composites. This new class of materials should not only possess higher strength-to-weight ratio than metals but also tailored with integrated intelligence, which is desirable as infrastructures for next generation of "internet of things." Carbon nanomaterials, such as carbon nanotubes and carbon nanofibers, have received dominant attention for the creation of intelligent composites. [3][4][5][6] They were dispersed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Thermoforming fabrication technology. Multiple studies have confirmed that thermoforming technology performs well during the fabrication of large-area interconnected circuitry 26 . The thermoforming process develops the 3-D shape of proposed components, using patterns fabricated on a planar substrate.…”
Section: Fabrication Of the 3-d Fssmentioning
confidence: 98%
See 2 more Smart Citations
“…Thermoforming fabrication technology. Multiple studies have confirmed that thermoforming technology performs well during the fabrication of large-area interconnected circuitry 26 . The thermoforming process develops the 3-D shape of proposed components, using patterns fabricated on a planar substrate.…”
Section: Fabrication Of the 3-d Fssmentioning
confidence: 98%
“…Several electronics, such as implantable neuro monitors and stimulators 20 , optoelectronic devices 21 and conformal photovoltaic devices 22 , have been fabricated utilizing these technologies, but the fabrication of large-scale electronic devices, such as FSSs, remains impractical due to the time consuming in the fabrication which also results in high fabrication cost. To address the large-scale manufacturing issue for 3-D devices, alternative solutions, such as aerosol jetting 23 , direct printing 24 and 3-D moulded interconnected devices 25,26 , have been proposed. While these proposals offer solid support for large-scale manufacturing of the metallic and insulator layers of electronic devices 26 , they remain immature and unable to fabricate complex electronics and electronic components that would serve actual industrial applications 26 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…61 Yang et al and Plovie et al documented an easily scalable approach that involves the combined use of the PCB technology inspired stretchable circuit and thermoforming technology for the creation of 3D sensory polymers and composites. 17,[84][85][86] This technology begins with fabricating the circuit on a rigid and planar carrier board, then transferring the circuit, and sandwiching it between thermoplastic polymers or composites using a Applied Physics Reviews REVIEW scitation.org/journal/are lamination process. The final thermoforming step shapes the sandwich structure by heating the encapsulating polymer beyond its glass transition temperature and pushing the polymer layers and the circuit toward the mold.…”
Section: A Geometry For Stretchable Environmental Sensorsmentioning
confidence: 99%
“…To ensure hermeticity, barrier layers have to be selected carefully. Polymers such as polyimide, polydimethylsiloxane (PDMS), and parylene types are well known for their use in the development of flexible or stretchable implantable electronic [8][9][10]. However, these polymers do not meet the stringent barrier requirements (very limited diffusion of water, ions, and molecules) to act as barrier layers for long-term implantation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%